THE INFLUENCE OF EASE OF USE ON BUYING INTERESTS IS MEDIATED BY TRUST - Anggraini, Sella Tri; Fikriah, Nur Laili (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study's objective is to investigate the relationship between  ease of use and buying interest, with the latter being mediated by trust in TikTok Shop customers as the subject of the studyIn the course of this research, a path analysis was performed with the help of the SmartPLS 3.0 program. In order to conduct this research, a sampling strategy known as purposeful sampling was used to select 240 users from the TikTok Shop. The findings of this study indicate that ease of use and trust both have an effect on buying interest. The ease of use are indirectly impacted by trust.